Evolution of acoustic communication and habitat type influence in the avian species, sabota lark calendulauda sabota (alaudidae) - Madiseng, Mogaletloa Eugene (My University, 2024)
Habitat acoustics has been proposed to be involved in producing selective forces that mould bird vocalisations into the sounds we hear when birds vocalise. The influence of habitat on bird vocalisations is well-documented, mostly in bird species in the Americas rather than in Africa. The Sabota Lark Calendulauda sabota is near-endemic to southern Africa and has a widespread distribution in habitats ranging from well-developed Savanna woodland to Karoo and semi-desert scrub. However, to my knowledge, no records of published studies have endeavoured to quantitatively describe the vocal structure of the Sabota Lark or the effects of habitat on its vocalisations. This makes the Sabota Lark an ideal candidate to investigate the effect of habitat type and structure on bird vocal structure. This study investigated the effect of habitat on the vocalisations of the Sabota Lark and whether the Acoustic Adaptation Hypothesis applies to the Sabota Lark. Fieldwork was conducted during breeding seasons in the sites that represented semi-arid (Vachellia) and moist Savanna (broad-leaved woodland) and the dry Nama Karoo shrublands. Songs were analysed using a bioacoustics sound analyses software. A total of 992 song strophes were extracted, and spectrograms were generated from which descriptions of songs were done. Seven spectrogram parameters of 878 song strophes were analysed using univariate one-way ANOVA and t-test. Multivariate (Principal Component Analyses – PCA and Linear Discriminant Analyses – LDA) statistical analyses were performed in two parts to respectively include: 1) analyses of a comprehensive dataset with all the remaining seven vegetation types included and 2) analyses of a reduced dataset comprising only the two vegetation types with the highest sampling (viz., Bushmanland Basin Shrubland – BBS and Musina Mopane Bushveld – MMB). The Sabota Lark emerged as a species with large and complex song variations between individual birds and within and between different habitat types. The individuals gave many unique song types and song strophes. Furthermore, this species explored both types of song presentation or singing styles as some individuals repeated song types at least twice before switching to another song type. This singing style is called “eventual variety”. The vi other birds rendered their song types once and never twice in succession. This is called “immediate” variety, meaning they switched to new song types immediately without repeating songs that have already been sung. This was observed both within individuals and among individuals in different habitat types. The means of the parameters of song strophes of the Sabota Larks among the vegetation types were highly significantly different, indicating that variances in songs between vegetation types were not equal. However, most parameters were significantly different contrary to the study predictions; Therefore, future studies should include a large sample size with equal representation across habitats, and the vegetation structure should be quantified
Thesis (M. Sc. (Zoology) -- University of Limpopo, 2024
Keywords: Avian species; Sabota lark calendulauda sabota (alaudidae); Habitat acoustics; Larks; Birds -- South Africa; Birds -- Habitat